PENGARUH KOMPETENSI DAN KOMITMEN KEPALA SEKOLAH TERHADAP PRESTASI KERJA GURU DI SMK NEGERI KOTA PONTIANAK - Yuli Suherni; Sukmawati Sukmawati; Muhammad Chiar (Universitas Tanjungpura, 2020)
AbstractThe purpose of this research were to describe how the principal's commitment to the achievement of teachers at SMK Kota Pontianak, the principal's commitment to the achievement of teachers at SMK Kota Pontianak, and the competence and commitment of the principal to the achievement of teachers in SMK Kota Pontianak. This form of research used a quantitative approach. There were two free variables and one bound variable. Free variable is the competence of the principal declared X1 and the principal's commitment is declared X2. The bound variable was the achievement of the teacher's stated work Y. In this study instrument competency variables, commitment variable instruments and instrument variables of teacher's work achievement in the test were evaluated for its validity and realibility. The results of the study showed that, the influence of the competence of the principal (X1) had a significant effect on the achievement of teacher (Y) Beta (b1) by 0.433 = 43.3 %, the influence of principal commitment (X2) affects teacher work performance (Y) Beta (b1) by 0.443 = 44.3%, the effect of competency (X1) and principal commitment (X2) on teacher work performance (Y) amounted to 0.681 or 68.1%. F test results were seen in the ANOVA output of the results of linear regression analysis multiple times take F count > F table 72.588 > 3.13 Keywords: Competence, Commitment, Teacher Work Achievement.